Diastolic function in heart transplant: From physiology to echocardiographic assessment and prognosis - Sciaccaluga, Carlotta; Fusi, Chiara; Landra, Federico; Barilli, Maria; Lisi, Matteo; Mandoli, Giulia Elena; D’Ascenzi, Flavio; Focardi, Marta; Valente, Serafina; Cameli, Matteo (Frontiers in Cardiovascular Medicine, 2022)
Heart transplant (HTx) still represents the most effective therapy for end-stage heart failure, with a median survival time of 10 years. The transplanted heart shows peculiar physiology due to the profound alterations induced by the operation, which inevitably influences several echocardiographic parameters assessed during these patients’ follow-ups. With these premises, the diastolic function is one of the main aspects to take into consideration. The left atrium (LA) plays a key role in this matter, and that same chamber is significantly impaired with the transplant, with different degrees of altered function based on the surgical technique. Therefore, the traditional echocardiographic evaluation of diastolic function applied to the general population might not properly reflect the physiology of the graft. This review attempts to provide current evidence on diastolic function in HTx starting from defining its different physiology and how the standard echocardiographic parameters might be affected to its prognostic role. Furthermore, based on the experience of our center and the available evidence, we proposed an algorithm that might help clinicians distinguish from actual diastolic dysfunction from a normal diastolic pattern in HTx population.